Spinal Reflex Control of Arterial Blood Pressure: The Role of TRP Channels and Their Endogenous Eicosanoid Modulators - Minic, Zeljka; O’Leary, Donal S.; Reynolds, Christian A. (Frontiers in Physiology, 2022)
The spinal cord is an important integrative center for blood pressure control. Spinal sensory fibers send projections to sympathetic preganglionic neurons of the thoracic spinal cord and drive sympathetically-mediated increases in blood pressure. While these reflexes responses occur in able-bodied individuals, they are exaggerated following interruption of descending control – such as occurs following spinal cord injury. Similar reflex control of blood pressure may exist in disease states, other than spinal cord injury, where there is altered input to sympathetic preganglionic neurons. This review primarily focuses on mechanisms wherein visceral afferent information traveling via spinal nerves influences sympathetic nerve activity and blood pressure. There is an abundance of evidence for the widespread presence of this spinal reflex arch originating from virtually every visceral organ and thus having a substantial role in blood pressure control. Additionally, this review highlights specific endogenous eicosanoid species, which modulate the activity of afferent fibers involved in this reflex, through their interactions with transient receptor potential (TRP) cation channels.